Dynasties and democracy : the inherited incumbency advantage in Japan - Smith, Daniel M., 1982- (Studies of the Walter H. Shorenstein Asia-Pacific Research Center., 2018)
The presence of dynasties seems to run counter to widely held conceptions of democratic opportunity and fairness. Yet they persist throughout the modern democratized world. Looking at the institutional change in Japan's party system as a comparative model, Daniel M. Smith examines the factors that contribute to their development over time and space and the advantages that members of dynasties reap throughout their political careers.